Authoritarian legislature, legitimacy strategy, and shadow economy. Issue 6 (18th August 2022) - Kim, Da Sul; Moon, Chungshik
ABSTRACT: How do the electoral institutions in authoritarian regimes affect the development of the shadow economy? While understanding the determinants of the shadow economy is important for the study of political economy and development, little is known about the political determinants of the shadow economy. We argue that authoritarian governments reduce the size of the shadow economy through legislatures. Electoral institutions allow regimes to strengthen their claim to performance legitimacy as they need to cater to a larger winning coalition. This results in increased spending on domestic socio-economic policies that effectively reduce the size of the shadow economy. Using panel data of 54 authoritarian regimes between the years 1991 and 2010, we find authoritarian regimes with electoral institutions have a significant, negative effect on the size of the shadow economy. This study has important implications for understanding the determinants of the shadow economy as well as the effect of political contestation in authoritarian regimes.